2017
DOI: 10.1177/1178630217716917
|View full text |Cite
|
Sign up to set email alerts
|

Management of Empty Pesticide Containers—A Study of Practices in Santa Cruz, Bolivia

Abstract: The mismanagement of empty containers of pesticides, posing a risk to the environment and the health of people, has motivated the promotion of international policies and guidelines to mitigate such problems. Despite these guidelines, attention to this problem is inadequate in Bolivia. The objective was to study the knowledge and practical management of the containers and to implement a responsible management plan for empty pesticide containers. METhodS: This study implemented the project from 2014 to 2016 in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It is highly unlikely that such knowledge exists among the subjects in our study. In order to discourage the recycling of empty containers and their use to store food and water, Huici et al (2017) reported training sessions in Bolivia focused on the proper management of empty pesticide containers, with triple rinsing and puncturing of the containers to prevent reuse.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly unlikely that such knowledge exists among the subjects in our study. In order to discourage the recycling of empty containers and their use to store food and water, Huici et al (2017) reported training sessions in Bolivia focused on the proper management of empty pesticide containers, with triple rinsing and puncturing of the containers to prevent reuse.…”
Section: Discussionmentioning
confidence: 99%
“…In using MEMC in sugarcane plantations, cases of mercury poisoning may occur if a farm worker comes into contact with Shirtan 1 via ingestion or dermal absorption, either through the skin or orally. This is a concern as it is not uncommon for chemical users to apply or dispose of hazardous chemicals incorrectly (Calliera et al, 2013;Huici et al, 2017;Bagheri et al, 2021). Although modern information and regulations imposed on the handling of mercury pesticides in Australia are comprehensive, they require workers to strictly follow procedures.…”
Section: Mercury Toxicity To Corals Of the Great Barrier Reefmentioning
confidence: 99%
“…A study on pesticide control policies in European countries identified differences in policies and public debates, including that despite the different policies adopted, public debates and regulations are increasing, indicating the need for greater data sharing [35]. A study conducted in Bolivia pointed that the main gaps on agrochemicals reverse supply chain are lack of knowledge and precise lines for farmers [36]. Zhao et al [37] conducted a case study creating a simulator called i-certificate, which encompasses a blockchain to promote voluntary adoption of renewable energy.…”
Section: Related Workmentioning
confidence: 99%